Predominance of industrial Pb in recent snow (1994-2004) and ice (1842-1996) from Devon Island, Arctic Canada - Shotyk, William; Zheng, Jiancheng; Krachler, Michael; Zdanowicz, Christian; Koerner, Roy M.; Fisher, David (Geophysical research letters, 2005)
Atmospheric Pb contamination was studied using snow and ice from the Canadian arctic. Forty-five samples representing the past ten years of snow accumulation on Devon Island contain an average of 45.2 pg/g of Pb but only 0.43 pg/g of Sc. The average ratio of Pb to Sc (105) is far greater than that of soil-derived dust particles (in the range 1 to 5) which indicates that ca. 95 to 99% of recent Pb is anthropogenic. Isotopic analyses (206Pb, 207Pb, 208Pb) confirm that anthropogenic sources continue to dominate atmospheric Pb inputs. Unlike snow from Greenland which receives Pb predominantly from the U.S. (206Pb/207Pb ≈ 1.2), snow from Devon Island is less radiogenic (206Pb/207Pb ≈ 1.15). There are pronounced seasonal variations, and the snow samples containing the greatest Pb enrichments are from winter when the Arctic is dominated by air masses originating in Eurasia. While the elimination of gasoline lead additives in Europe, North America and Japan has helped to reduce Pb emissions during the past two to three decades, aerosols in the Arctic today are still highly contaminated by industrial Pb.